Form 27 in the Indian Patent System (Journal of Intellectual Property Rights (JIPR), 2025)
The Indian patent regime mandates transparency in the working of patented inventions through periodic disclosures by patentees. The recent declaration of the Patents (Amendments) Rules, 2024, has introduced significant modifications to the procedural and substantive requirements for filing Form 27, the annual working statement.1 This manuscript provides a comprehensive overview of Form 27’s legal basis under THE PATENTS ACT, 1970, its purpose, the implications of recent amendments, and the evolving jurisprudence surrounding compulsory licensing and patent working. It also critically examines the concerns related to confidentiality and data transparency, aligning with the provisions of the Right to Information Act, 2005.